2009
DOI: 10.1111/j.1365-2133.2009.09512.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic indications that human sweat glands are a rich source of nestin-positive stem cell populations

Abstract: This pilot study provides the first, simple protocol for the isolation of adult human nestin-positive stem cells from the sweat gland mesenchyme, which promises to provide an easily accessible and abundantly available, autologous source of multipotent stem cells for cell-based regenerative medicine applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…[17][18][19][20] Recently, several studies demonstrated similar nestinpositive stem cell populations present mainly in the follicular bulge and connective tissue sheath, human sweat glands, as well as randomly distributed in small numbers throughout the interfollicular dermis. 1,2,5,[20][21][22][23][24][25][26] In cutaneous malignancies, studies have demonstrated up-regulated nestin expression in melanomas, cutaneous peripheral nerve sheath tumours such as malignant peripheral nerve sheath tumour, and also mesenchymal tumours such as dermatofibrosarcoma protuberans. 4,[27][28][29] Although few studies have examined the expression of CK15 and CK19 in basal cell carcinoma (BCC) and SCC, only rarely have nestin expression been examined in the two most common cutaneous malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Recently, several studies demonstrated similar nestinpositive stem cell populations present mainly in the follicular bulge and connective tissue sheath, human sweat glands, as well as randomly distributed in small numbers throughout the interfollicular dermis. 1,2,5,[20][21][22][23][24][25][26] In cutaneous malignancies, studies have demonstrated up-regulated nestin expression in melanomas, cutaneous peripheral nerve sheath tumours such as malignant peripheral nerve sheath tumour, and also mesenchymal tumours such as dermatofibrosarcoma protuberans. 4,[27][28][29] Although few studies have examined the expression of CK15 and CK19 in basal cell carcinoma (BCC) and SCC, only rarely have nestin expression been examined in the two most common cutaneous malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 5 hSGSCs are stained for Nestin, which is expressed by more than 80 % of cells in an hSGSCs culture [28]. Neurites, marked with β3-Tubulin, aligned with the orientation of hSGSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, hSGSCs represent a promising source of autologous stem cells for cell replacement therapies. A biopsy of human axillary skin is sufficient and avoids any surgical intervention [28]. In an in vivo full-thickness skin defect, hSGSCs were able to improve vascularisation during scaffold-dependent dermal regeneration [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we applied isolation procedures and propagation methods for the harvesting of mammary stem cells similar to those we have already established for pancreatic, submandibular or sweat gland-derived stem cells [26,29,33]. We opted to isolate stem cells from the mammary tissue of female and male donors via adherence to conventional cell culture plastic, similar to the methods we used for the other glandular stem cells and also similarly applied by Cregan and colleagues for breast milk-derived stem cells [21].…”
Section: Introductionmentioning
confidence: 99%